Ramrod: an experimental multi-microprocessor - Rabinowitz, Alan Errol (My University, 2015)
The computer architect of the 80's races apparently intractable dilemma: Computer manufacturers have to contend with the soaring costs incurred in producing custom-made chips, and would prefer to use commercially-available, state-of-the art, large-scale integrated circuits. Product users, however demand highly reliable, realistically- priced systems which are nevertheless flexible enough to meet changing needs.
Keywords: Software architecture; Electronic data proccessing